2015
DOI: 10.4103/2008-7802.153537
|View full text |Cite
|
Sign up to set email alerts
|

Preventive role of estradiol on kidney injury induced by renal Ischemia-Reperfusion in male and female rats

Abstract: Background:Renal ischemia-reperfusion (RIR) is the main cause of renal failure. The incidence of RIR injury seems to be gender-related due to female sex hormone; estrogen. This study was designed to investigate the protective role of estrogen against RIR injury in male and ovariectomized female rats.Methods:Thirty-nine Wistar rats were used in this study as male and ovariectomized female rats in the sham-operated, RIR, and estradiol-treated plus RIR groups. The RIR was induced by clamping the renal vessels for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 39 publications
(45 reference statements)
2
17
0
Order By: Relevance
“…In addition, protective effects of testosterone were approved in renal ischemia-reperfusion model (47). Similarly, a recent study detected that estrogen 500 mg/kg decreased renal damage in ischemia-reperfusion model and its administration improved proteinuria and renal damage (48). A robust finding of this study was the increase of renal SOD activity in female rats after the administration of the vitamins, while this effect was not observed in male rats.…”
Section: The Effect Of Gentamicin On Kidney Mda Level and Kidney Sod supporting
confidence: 55%
“…In addition, protective effects of testosterone were approved in renal ischemia-reperfusion model (47). Similarly, a recent study detected that estrogen 500 mg/kg decreased renal damage in ischemia-reperfusion model and its administration improved proteinuria and renal damage (48). A robust finding of this study was the increase of renal SOD activity in female rats after the administration of the vitamins, while this effect was not observed in male rats.…”
Section: The Effect Of Gentamicin On Kidney Mda Level and Kidney Sod supporting
confidence: 55%
“…Takaoka et al [ 34 ] and Tanaka et al [ 35 ] demonstrated with the renal pedicle occlusion model that male rats injected with estrogen 15 min prior to reperfusion demonstrated improved post-ischemic renal outcomes. On the other hand, a recent study which employed intramuscular injection of estrogen 3 days prior to renal ischemia-reperfusion surgery found that estrogen’s protective effect was limited to ovariectomized female rats and did not protect male rats [ 36 ]. The discrepancy of these findings is probably due to the heterogeneity of the experimental model and the length of time of administration.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy of these findings is probably due to the heterogeneity of the experimental model and the length of time of administration. Estrogen dose varied according to the study (25 ÎŒg/kg × 7 days [ 10 ], 40–500 ÎŒg/kg × 14 days [ 11 ], 100 ÎŒg/kg × single dose [ 35 ] and 500 ÎŒg × 3 days [ 36 ]); however, no prior study has evaluated the effect of estrogen administration after reperfusion, either whole-body ischemia/reperfusion or renal vascular occlusion. In the present study, only higher dose of estrogen (400 ÎŒg/kg) injected during the early reperfusion phase improved the renal outcome in male mice.…”
Section: Discussionmentioning
confidence: 99%
“…These observations were in agreement with others. [ 15 16 17 18 ] There are some reports suggesting that ET-1 is involved in the development of postischemic ARF in clinical transplantation. [ 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 51 ] Previous studies have demonstrated that testosterone has an important role in increasing the susceptibility to ischemic renal injury. [ 52 53 ] By contrast, other experimental results suggest that estrogen has a protective effect in ischemic renal injury in female[ 18 ] via suppression of ET-1 production and activation of the phopsphatidylinositol-3 kinase/protein kinase B signaling pathway. [ 54 55 ] Our result showed no difference in nitrite level between the male and female groups, and kidney MDA level reduced only in male, but other study showed that kidney MDA level decreased in male and female ischemic animals,[ 17 ] and IR decreased serum and kidney level of nitrite.…”
Section: Discussionmentioning
confidence: 99%